Patients’ Perception of the Quality of Psychiatric Services: A Study at the Accra Psychiatric Hospital - Atindanbila, S. (University of Ghana, 2000)
The study was aimed at gathering information on clients' perception of the quality of psychiatric services rendered to them at the outpatients’ department of the Accra psychiatric Hospital. The data was collected with the aid of a structured interview schedule. The main findings were that clients are generally satisfied with the quality of services rendered to them at the Psychiatric Hospital on most of the indices used. However, they had dissatisfaction in the following areas: No investigations ordered for them, their diagnosis not explained to them and there were no home visits by the health professionals. It was also realized that the clients did not have much knowledge regarding other important professionals in the Psychiatric Hospital like the clinical Psychologists, Psychiatric Social Workers and Community Psychiatric Nurses whose services they may need. It also indicated areas of further study like finding out why almost all the clients complement the Hospital treatment with traditional medicine.
Keywords: Psychiatric Services; Psychiatric Hospital; Perception of the Quality of Psychiatric Services; Psychiatric Social Workers